Effect of isoniazid and its compositions with oxidized dextran on the activity of inflammation and destruction processes in the liver of mice with BCG granulomatosis - A. M. Sinyavskaya; A. V. Troitskii; T. N. Bystrova; V. G. Selyatitskaya; V. A. Shkurupy (Acta Biomedica Scientifica)
Introduction. Tuberculosis is among the most common infectious diseases in humans. One of the main drugs for treating tuberculosis, isoniazid, has a wide range of adverse effects, including hepatotoxicity, making the search for ways to reduce its toxic reactions highly relevant. The aim of the study was to assess liver damage, as well as the levels of the cytokines IL-6 and TNF-α, metalloproteinases MMP1 and MMP9, and the protease inhibitor TIMP-1 in mice with BCG granulomatosis. These factors were evaluated immunohistochemically following intraperitoneal injection of isoniazid, dextrazide, or a liposomal form of dextrazide (LFD), along with its inhalational injection. Methods. Fifty male BALB/c mice were infected with BCG vaccine via retroorbital route. After 3 months, isoniazid or its compositions with oxidized dextran were injection twice a week at a dose of 14 mg/kg body weight for 2 months; the control group received NaCl solution. Liver was followed by histological processing and immunohistochemistry. Results. Tuberculosis granulomas were detected in the liver 5 months after infection. The total number of granulomas was reduced in mice receiving all forms of isoniazid, but LFD injection by inhalation was the most effective. The volume densities of lymphoid infiltrates and tissue damage were greatest in the livers of mice injected with NaCl, with lower values observed in the isoniazid-treated groups. The number of cells producing IL-6, MMP1, and MMP9 was highest in the isoniazid group, while TNF-α production was highest in the NaCl group. The lowest values for these parameters were observed in mice treated with LFD. The number of cells producing TIMP1 was highest in the groups receiving LFD. Conclusion. Two months after starting the isoniazid treatments, the amount of mycobacterium tuberculosis (MBT) in the liver decreased, particularly with the inhalational injection of LFD. This suggests that LFD helps modulate the inflammatory response in tissues and reduces damage, likely due to the systemic anti-inflammatory effect of oxidized dextran in the LFD.